Miniantrostomy for the reduction of fractures of the orbital floor - M. B. O’Regan, * S. P. R. MacLeod (Blackwell Synergy, 2000)
The prime goals in managing a fracture of the orbital floor are repositioning of the displaced orbital tissues, restoration of the previous orbital volume and shape, and provision of an orbitoantral partition. This is ideally done using autogenous materials.